1997
DOI: 10.1007/bf02490873
|View full text |Cite
|
Sign up to set email alerts
|

Coupling protocol for thin layer chromatography/matrix-assisted laser desorption ionization

Abstract: SummaryThis paper reports the investigation and optimization of the thin layer chromatography/matrix-assisted laser desorption/ionization (TLC-MALDI) coupling protocol. The fundamental coupling parameters which influence sensitivity and lateral analyte spreading are extraction solvent selection, extraction time, and pressure. Selection of the solvent is dependent upon its extraction efficiency, which has been correlated with extraction solvent Rf value. Maximum extraction efficiency occurs after two minutes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Methods for separation of gangliosides by thin layer chromatography (TLC) are well established [14,[43][44][45], and previous work in our own and in other laboratories has shown that TLC can be easily coupled to MALDI-TOF MS [31,46,47], with some compromise in instrument performance due to the irregular surface [31]. The ability to desorb gangliosides without fragmentation, as shown here, allows coupling TLC separations to MALDI-FTMS while retaining spectral quality.…”
Section: Resultsmentioning
confidence: 93%
“…Methods for separation of gangliosides by thin layer chromatography (TLC) are well established [14,[43][44][45], and previous work in our own and in other laboratories has shown that TLC can be easily coupled to MALDI-TOF MS [31,46,47], with some compromise in instrument performance due to the irregular surface [31]. The ability to desorb gangliosides without fragmentation, as shown here, allows coupling TLC separations to MALDI-FTMS while retaining spectral quality.…”
Section: Resultsmentioning
confidence: 93%
“…The dependence of the RSD of the analyte/IS ratio on the number of laser shots was studied by Gusev et al [107,132]. The authors found that the maximum signal intensity was obtained for first 40 laser shots, and the lowest RSD was achieved for the 40 laser shots after the first ten.…”
Section: Quantitative Characterization By Maldimentioning
confidence: 97%
“…Both conditions must be fulfilled without major spreading of the analyte during the addition of the solvents, i.e., without compromising the achieved quality of chromatographic separation. Both important prerequisites were discussed in more detail in (Mehl et al 1997). …”
Section: Tlc/maldi Combinationmentioning
confidence: 98%